2010
DOI: 10.1186/1752-0509-4-50
|View full text |Cite
|
Sign up to set email alerts
|

A formal model for analyzing drug combination effects and its application in TNF-α-induced NFκB pathway

Abstract: BackgroundDrug combination therapy is commonly used in clinical practice. Many methods including Bliss independence method have been proposed for drug combination design based on simulations models or experiments. Although Bliss independence method can help to solve the drug combination design problem when there are only a small number of combinations, as the number of combinations increases, it may not be scalable. Exploration of system structure becomes important to reduce the complexity of the design proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 41 publications
0
42
0
Order By: Relevance
“…Once again, 10-nm and 20-nm AgNPs demonstrated more-significant reductions in biofilm recovery when combined with lower concentrations of aztreonam than did 40-nm and 60-nm nanoparticles. Next, we used the Bliss independence model (22,37,54) and FIC index (24,39,40) to calculate synergy between AgNPs and aztreonam in the inhibition of P. aeruginosa biofilm biomass ( Fig. 6 and Table 3), and we confirmed that 10 nm was the optimal AgNP size to use in the antimicrobial combination.…”
Section: Discussionmentioning
confidence: 84%
“…Once again, 10-nm and 20-nm AgNPs demonstrated more-significant reductions in biofilm recovery when combined with lower concentrations of aztreonam than did 40-nm and 60-nm nanoparticles. Next, we used the Bliss independence model (22,37,54) and FIC index (24,39,40) to calculate synergy between AgNPs and aztreonam in the inhibition of P. aeruginosa biofilm biomass ( Fig. 6 and Table 3), and we confirmed that 10 nm was the optimal AgNP size to use in the antimicrobial combination.…”
Section: Discussionmentioning
confidence: 84%
“…Synergism and additivity were calculated as recently published using the following formula: S = r(a, b) -r(a0, b) × r(a, b0). 45,46 Foci assay For γH2AX/53BP1 and pDNA-PKcs T2609 foci assay 4 × 10 5 cells per well were grown in 3D lrECM for 24 h, then treated with antibodies (AIIB2 or IgG#1: 10 μg/ml) and inhibitor (Olaparib or DMSO: 1 μM; 24 h) and irradiated with 6 Gy or left unirradiated. Twenty-four hours after irradiation, cells were isolated using trypsin/EDTA, fixed with 3% formaldehyde/ phosphate-buffered saline (Merck, Darmstadt, Germany) and permeabilized with 0.25% Triton-X-100/phosphate-buffered saline (Roth, Karlsruhe, Germany).…”
Section: Total Protein Extraction Western Blottingmentioning
confidence: 99%
“…A number of other supra-additive synergy models have been advanced (30,32,42,74,76,92,148,150,174). I briefly review four, the first three of which are closely related to Loewe additivity.…”
Section: Other Additivitiesmentioning
confidence: 99%
“…Bliss additivity is often used in the analysis of synergy in antimicrobiology, toxicology, radiation medicine, and other fields (20,39,60,64,123,124,152,174,177). According to Yeh et al (176), an advantage of Bliss additivity is that it is exactly analogous to the definition of epistasis used in molecular biology.…”
Section: Bliss Additivitymentioning
confidence: 99%